Decreased Netrin-1 and Correlated Th17/Tregs Balance Disorder in Aβ1–42 Induced Alzheimer’s Disease Model Rats - Sun, Lina; Ju, Ting; Wang, Tianhang; Zhang, Liang; Ding, Feifan; Zhang, Yan; An, Ran; Sun, Yilei; Li, You; Lu, Yidan; Zhang, Xin; Chi, Lijun (Frontiers in Aging Neuroscience, 2019)
There is increasing evidence indicating that inflammation represents a key pathological component of Alzheimer’s disease (AD). A possible factor that may contribute to this process is netrin-1, a neuronal guidance molecule. This molecule has been shown to exert an unexpected immunomodulatory function. However, the potential changes and correlations of netrin-1 with T helper 17/regulatory T cells (Th17/Tregs) as related to inflammation in AD has yet to be examined. In this study, netrin-1 and Th17/Tregs balance were investigated, and the relationship among netrin-1, Th17/Tregs and cognitive function were analyzed in a rat model of AD. In this model, a bilateral intracerebroventricular administration of Amyloid β1-42 (Aβ1-42) was used to produce spatial learning and memory deficits, as well as increased neuronal apoptosis, which were detected 7 days after injection for AD7d group and 14 days for AD14d group. Netrin-1 concentrations were significantly down regulated in both serum and cerebrospinal fluid (CSF) of these AD rats, effects which were strongly correlated with cognitive deficits. Increased levels of interleukin (IL)-17 and deceased IL-10 were observed in both the circulation and CSF and were also correlated with the percent of time spent in the target quadrant of AD in these rats. These changes resulted in netrin-1 concentrations being negatively correlated with IL-17 but positively correlated with IL-10 concentrations in the serum and CSF. We also found that the Th17/Tregs balance was disrupted in these AD rats. Collectively, these findings reveal that the reduction in netrin-1 and correlated disruption of Th17/Tregs balance in AD rats, may diminish the immunosuppressive effect of netrin-1 on Th17/Tregs in AD pathogenesis.